Effect of High Performance Work Practices on Job Embeddedness and Employee Innovative Behavior - Ansari, Nabeel Younus; Siddiqui, Shakira Huma; Farrukh, Muhammad (International Journal of Contemporary Economics and Administrative Sciences, 2018)
Purpose – This study ascertained the high performance work practices effects on employee innovative behavior through key mediating role of the job embeddedness of front line service employees in Pakistan hospitality sector. Method – Data gathered from four and five-star hotel FLSEs in two waves with a time lag of two weeks, the relationships in the conceptual model were gauged through Partial Least Squares (PLS). Findings – The results suggest that job embeddedness mediate the relationship between high performance work practices and employee innovative behavior. In particular, front line service employees in presence of high performance work practices have high job embeddedness, and are more likely to exhibit innovative behaviors at work. Research implications – This study will send a strong message to service firms that provision of performance enhancing human resource practices is of prime importance to enhance. With this in mind management needs to take benefit of the strength of high performance work practices to enhance frontline employees attachment with organization to produce innovation related behaviors at work